Non-Greedy Routing And Admission Control Algorithm For Traffic Engineering In MPLS Networks - Tan, Su Wei (2002)
This thesis presents a new routing and admission control algorithm for dynamic routing of bandwidth-guaranteed Label Switched Paths ( LSPs) in Multi_Protocol Label Switching (MPLS) networks. The bandwidth-guaranteed LSPs are useful for traffic engineering applications, delivery of multimedia traffic that required service assurance, and implementation of Virtual Private Networks (VPNs). Our proposed algorithm works online I.e. handle requests arriving one-by-one without the knowledge of future traffic arrival. It is designed based on two previously developed routing concepts: minimal interference routing and non-greedy admission control scheme. The minimal interference routing concepts considers the knowledge of ingress-egress points to defer loading on certain critical links. These critical links are defined as links that, if heavily loaded, would make it impossible to satisfy future demands between certain ingress-egress pairs. On the other hand, the non-greedy framework suggests the use of exponential function to convert utilisation into link cost, and performs admission control based on the computed path cost. Our new algorithm is derived from the observations of the success and failure of both strategies. In particular , we develop a new weight assignment scheme, which is based on the objectives to minimise interference under low network loading , and resource usage under high network loading. We also propose a new admission control strategy that can achieve fair acceptance rate for ingress-egress pairs with diffent hop distances. The performance evaluation is carried out through an extensive set of simulation experiments. A flow-level event-driven routing simulator was developed specifically for the evaluation. We compare the performance of the algorithm with several previously proposed algorithms under a wide range of operating conditions. The simulation results show that our algorithm out -performs other strategies on several metrics, like the bandwidth blocking probability, fairness, and successful rerouting of demands upon link failure. In addition, the algorithm is capable of protecting LSP setup requests for certain ingress-egress pairs that have higher priority level.